2009
DOI: 10.1029/2009gl039442
|View full text |Cite
|
Sign up to set email alerts
|

Tracing solar wind plasma entry into the magnetosphere using ion‐to‐electron temperature ratio

Abstract: When the solar wind Mach number is low, typically such as in magnetic clouds, the physics of the bow shock leads to a downstream ion‐to‐electron temperature ratio that can be notably lower than usual. We utilize this property to trace solar wind plasma entry into the magnetosphere by use of Cluster measurements in the vicinity of the dusk magnetopause during the passage of a magnetic cloud at Earth on November 25, 2001. The ion‐to‐electron temperature ratio was indeed low in the magnetosheath (Ti/Te ∼ 3). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…next paragraph), and their intermittent observation may be due to small-scale changes in the distance from the magnetopause to the spacecraft not accounted for in the MHD simulation. The reader is referred to Lavraud and Borovsky [2008] for aspects related to enhanced flows and associated magnetopause wave activity during low M A (see also Chen et al [1993], Lavraud et al [2009] and Taylor et al [2012]). However, this topic is beyond the focus of the present study.…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%
“…next paragraph), and their intermittent observation may be due to small-scale changes in the distance from the magnetopause to the spacecraft not accounted for in the MHD simulation. The reader is referred to Lavraud and Borovsky [2008] for aspects related to enhanced flows and associated magnetopause wave activity during low M A (see also Chen et al [1993], Lavraud et al [2009] and Taylor et al [2012]). However, this topic is beyond the focus of the present study.…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%
“…Table 1 lists some plasma parameters in auroral regions where T e0 > T i0 , calculated from measurements by the GEODESIC rocket (Burchill et al, 2004), the Freja satellite , and the FAST satellite (Ergun, 1999), respectively. By contrast, in most magnetosphic plasmas (especially encountering some extreme situations like, e.g., substorms), ξ T lies between 1/12 and 1/3, as reported by, e.g., AMPTE/IRM and Cluster observations in the Earth's central plasma sheet, the sheet boundary layers, and magnetosheath (Baumjohann, 1993;Phan et al, 1994;Lavraud, 2009). It is another interesting topic on the excitation of oscillitons under the condition of ξ T < 1, besides the case introduced in this paper with ξ T > 1.…”
Section: A Preliminary Simulation To Observationsmentioning
confidence: 97%
“…Since the concept of solar atmosphere extension and expansion into interplanetary space [18] endorsed by Pioneer V [19], showed to contain loopholes [20], and Magnetosphere breached continually by solar wind in several places [21], it is suggested that, both the flow of energetic protons [22], and energetic electrons >200 keV [23], in Magnetosheath, and the concentration of high density solar wind positive ion ranging between 35 to 127 cm -3 at Magnetosheath [22], contrary to background proton's density of 5-10 cm -3 [24], and Magnetosheath plasma interaction with magnetosphere at magnetopause, which results in fluctuations and strong magnetic fields, leading to an intense geomagnetic storm Dst<200 n Tesla [25], a situation which is similar to the ionospheric elongated diamagnetic cavity created after High-altitude Nuclear Detonation (HND) [1], therefore it is suggested that, both MS and HND are similar in nature, and resulted from charged particles interaction with geomagnetic field.…”
Section: High-altitude Nuclear Detonations (Hnd) and Magnetic Storms mentioning
confidence: 99%
“…The frequency of the produced EMP is given by 1 EMP f Hz t = (15) External Magnetic Field-Moment Ions (ExMF MI ) production HND earlier geomagnetic disturbances thought to have one initial phase [10], but as shown in Figure 1, Starfish Prim, Checkmate and Kingfish resulted magnetic field at Johnston Island, showed two initial phases, followed by a slow decrease and subsequent lengthy recovery to ambient conditions [28], the fields shown in Figure 1, are similar in shape to the Dst with one Sudden Storm Commencement (SSC) [16], the first initial phase of Starfish Prim shown in Figure 1, measured 150 γ at H+3.6 seconds, followed by 290 γ at H+25 [28]; comparing this mechanism, with energetic electrons >200 keV at Magnetosheath which related to the magnetopause electron layer [23], or Magnetosheath plasma, that interacts with the magnetosphere at the magnetopause, and fluctuates with strong magnetic field, leading to an intense geomagnetic storm with Dst <200 n Tesla [25], which is similar to the energetic Magnetosheath protons [22], or the energetic protons first detected by Pioneer V, and later caused geomagnetic disturbance measured at Honolulu and shown in Figure 2A [17], all of which suggesting the production of an Interplanetary External Magnetic Field (I-ExMF) [12].…”
Section: Electromagnetic Pulse (Emp) Generationmentioning
confidence: 99%
See 1 more Smart Citation